NURSING STUDENTS’ PERCEPTION OF SPINE (SPEAK ENGLISH FOR PROFESSIONAL NURSES), AN ICONIC MODEL OF MALL - Harmanto, Margaretha Dharmayanti (LINGUISTIKA, 2018)
This study aimed to discover the students' perception of an iconic model for mobile assisted language learning. The Android application was developed to help nursing students who learn English for Specific Purposes (ESP) especially speaking. The data were obtained quantitatively. The instrument used was questionnaires which were distributed in two stages of the development process. The first was during the preliminary study and the second was distributed in the implementation stage. The result showed that the students perceived that the navigation pane, the screen design, the information presented, the media integration, and the overall functionality are good (4.1) out of the maximal score (5.00). In conclusion, SPINE application is also efficient and acceptable for the users in terms of its navigation pane, screen design information presentation, media integration, and overall functionality.